2016
DOI: 10.1038/nbt.3367
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the effects of drugs on the immune system

Abstract: Understanding how drugs affect the immune system has consequences for treating disease and minimizing unwanted side effects. Here we present an integrative computational approach for predicting interactions between drugs and immune cells in a system-wide manner. The approach matches gene sets between transcriptional signatures to determine their similarity. We apply the method to model the interactions between 1,309 drugs and 221 immune cell types and predict 69,995 known and novel interactions. The resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 67 publications
1
61
0
Order By: Relevance
“…As the 85 genes were derived from transplantation datasets and, likely incorporated signatures of ongoing allo-responses, we investigated whether kaempferol and esculetin could have specific effects on immune cells. We applied a recent developed immune-cell specific drug repurposing approach58 to evaluate putative immune modulatory actions of kaempferol and esculetin. Using this methodology we can identify specific immune cell subsets a drug may potentially influence.…”
Section: Resultsmentioning
confidence: 99%
“…As the 85 genes were derived from transplantation datasets and, likely incorporated signatures of ongoing allo-responses, we investigated whether kaempferol and esculetin could have specific effects on immune cells. We applied a recent developed immune-cell specific drug repurposing approach58 to evaluate putative immune modulatory actions of kaempferol and esculetin. Using this methodology we can identify specific immune cell subsets a drug may potentially influence.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of novel processes, such as TLR4-activated myeloid cells in egg allergy or IFN related pathways in baked egg tolerance, prompts further study using traditional experimental approaches that may change our understanding of the immunology of food allergy. And finally, a transcriptional signature of the aberrant response to egg, and common with other food allergies including peanut, could be used to identify drugs with opposing actions, a computational approach to drug repurposing that has led to discovery of new therapeutics for diseases such as inflammatory bowel disease [3133]. …”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of neutrophils from bone marrow to blood requires MIP-2 [29, 30]. Kopydlowski found that MIP-2 mRNA expression of peritoneal macrophages reached peak levels (15-60 folds) at 1-2 h after exposure to LPS in C3H/OuJ mice [31].…”
Section: Discussionmentioning
confidence: 99%